Impact of Time Management Behavior on Undergraduate Student’s Performance of Pokhara University - K.C., Bishnu Raj (Nepalese Journal of Management, 2025)
This study examines the time management behavior on undergraduate student’s performance of Pokhara University. Academic performance is the dependent variable. The selected independent variables are study time, time utilization, goal setting, stress management, technology use. The primary sources of data is used to assess the opinions of respondents regarding study time, time utilization, goal setting, stress management, technology use. The study is based on the primary data of 120 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of time management behavior on undergraduate student’s performance of Pokhara University. The study showed a study time is positively correlated to academic performance. This means that higher the level of study time, higher would be the academic performance. Similarly, Time utilization is positively related to academic performance indicating that higher the level of time utilization, higher would be the academic performance. Likewise, goal setting has positive relationship with academic performance. It shows that goal setting leads to an increase in the academic performance. Similarly, stress management has positive relationship with academic performance. It reveals that higher the level of stress management, higher would be academic performance. The result shows that there is positive relationship between technology use and academic performance. It shows that an increase in the level of technology leads to the increase in the academic performance.